Project-Based Assessment Blended Learning To Improve Students' Psychomotor Competence - Rahayu, Wening Patmi; Zutiasari, Ika; Ningsih, Giarti (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2022)
This research and development aim to produce an appropriate blended learning-based assessment project that can improve student competence. Project assignment by utilizing various contemporary applications such as Tik Tok, Instagram, and Youtube as a medium for product promotion. The data were researched and developed using Research and Development methods, the research model used was adopted from Borg & Gall. The feasibility of the development product in the form of an instrument was validated by a validator of assessment experts, validators of material experts. Student competence is measured by cognitive and psychomotor aspects. Data analysis by percentage and paired sample T-test analysis. The results of expert validation were declared "Very Feasible" with a score of 86.4% (cognitive) and 88.2% (psychomotor). The results of material expert validation were 89% (cognitive) and 87.5% (psychomotor) with the "Very Feasible" category. The results of the large class trial resulted in a score of 86.7% for the teacher's response and 88% for the student's response to the assessment instrument product. The increase in student competence is measured through project assignments, where the results of the calculation of the paired sample T-test show that there is a difference in the average score before and after using the assessment instrument in either the cognitive or psychomotor domain.